2005
DOI: 10.4049/jimmunol.175.5.2982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Castration on Thymocyte Development in Two Different Models of Thymic Involution

Abstract: Age-associated thymic involution is accompanied by decreased thymic output. This adversely affects general immune competence and T cell recovery following cytoreductive treatments such as chemotherapy. A causal link between increasing sex steroids and age-related thymic atrophy is well established. Although castration has been demonstrated to regenerate the atrophied thymus, little is known about how this is initiated or the kinetics of thymocyte regeneration. The present study shows that although castration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 69 publications
14
163
0
2
Order By: Relevance
“…Since immunity can be restored faster following chemotherapy and hemopoietic stem cell transplantation, using reversible sex steroid blockade (52,(75)(76)(77)(78), hemopoietic stem cell transplantation may be rendered safe enough to reinstate tolerance in some autoimmunity patients given a similar though less myeloablative regime. However, any underlying stromal defects must be considered, as their effects could be magnified following thymic hypertrophy, increasing the risk of relapse, particularly if stromal cells are incapable of expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Since immunity can be restored faster following chemotherapy and hemopoietic stem cell transplantation, using reversible sex steroid blockade (52,(75)(76)(77)(78), hemopoietic stem cell transplantation may be rendered safe enough to reinstate tolerance in some autoimmunity patients given a similar though less myeloablative regime. However, any underlying stromal defects must be considered, as their effects could be magnified following thymic hypertrophy, increasing the risk of relapse, particularly if stromal cells are incapable of expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the androgen receptor (AR) has been documented in lymphoid and nonlymphoid cells of thymus and bone marrow, but not in mature lymphocytes [24,25], suggesting that the major impact of androgens may be on the developmental maturation of T and B cells. Castration of male animals results in significant thymic enlargement and increase in thymus weight and thymocyte number [26][27][28], a phenomenon which is also observed in the setting of defective androgen action (the androgen-resistant testicular feminization mouse [29]. It has also been shown that androgen deprivation stimulates thymic T cell output and results in increased numbers of phenotypically naïve CD4+ and CD8+ peripheral T cells (approximately 2 weeks after castration) and enhances antigen-specific immune responses in postpubertal male mice [30].…”
Section: Gonadal Steroid Hormones Regulate Immune Responsesmentioning
confidence: 87%
“…For example bone marrow stromal cells isolated from old mice inefficiently secrete IL-7 (Heng et al, 2005;Stephan et al, 1998). A recent study reported that the production of B cells was rescued following transplantation of aged B lineage progenitors into a young but not an old environment (Labrie et al, 2004).…”
Section: Multiple Factors Direct the Age-related Decline In B Lymphopmentioning
confidence: 99%